2015
DOI: 10.1037/cdp0000018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a culturally informed intervention on abused, suicidal African American women.

Abstract: Background This study examined 1) the relative efficacy of a culturally-sensitive empowerment group intervention (Nia) aimed at increasing three protective factors—self-esteem, hopefulness, and effectiveness of obtaining resources—versus treatment as usual (TAU) for low-income, abused African American women who recently had attempted suicide and 2) the impact of participants’ readiness to change with regard to their abusive relationship and suicidal behavior on their levels of each protective factor in the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…In addition, our results are related to previous research indicating that religiosity is associated with worse overall functioning in the context of HIV (Cotton et al, 2006). Thus, our research and previous studies may partially explain why culturally sensitive interventions incorporating spiritual components for women exposed to adversity (Zhang et al, 2013) have found relatively weak changes in mental health (McCain et al, 2008;Taha et al, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, our results are related to previous research indicating that religiosity is associated with worse overall functioning in the context of HIV (Cotton et al, 2006). Thus, our research and previous studies may partially explain why culturally sensitive interventions incorporating spiritual components for women exposed to adversity (Zhang et al, 2013) have found relatively weak changes in mental health (McCain et al, 2008;Taha et al, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…The present findings suggest that it may be beneficial for intervention developers to explore how they can further engage women within their communities and spiritual networks. Previous group interventions with spiritual components have shown improvements in overall mental health among women exposed to adversity (McCain et al, 2008; Taha, Zhang, Snead, Jones, Blackmom, Bryant, & Kaslow, 2015; Zhang et al, 2013). Spiritually driven group-based interventions that build upon individual’s connection within their communities may prove advantageous for IPV-exposed women experiencing symptoms of GAD.…”
Section: Discussionmentioning
confidence: 98%
“…If the resources in the community are sufficient (meaning both available and appropriate), this will lead to an individual being able to use resources and consequently being able to tolerate his or her negative affect and distress (Chu et al, 2013; Davis et al, 2009; Taha et al, 2015). However, if the resources in the community are insufficient, there are fewer opportunities for the individual to seek out appropriate care, leading to a higher likelihood for a suicidal act.…”
Section: Discussionmentioning
confidence: 99%